Design method and preparation method of 1.8-4 [mu] m silicon-based lens anti-reflection film

By designing and preparing film layer structures, including materials such as SiO, Ge, ZnS, YbF3 and Al2O3, the problem of poor transmittance and binding force of silicon-based lens amphipathic films in the prior art is solved, and a high transmittance and good bonding film layer is achieved.

CN119511422AActive Publication Date: 2025-02-25安徽光智科技有限公司

Patent Information

Application Number
CN202411530067.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-25
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

The prior art is difficult to design and prepare a high transmittance silicon-based lens amphipathic film in the 1.8-4 μm band, and the bonding force between the film layer and the substrate is poor, which increases the production difficulty.

Method used

The film stack formula is used to design the film layer structure, including SiO as the base layer, Ge as the connecting layer, ZnS and YbF3 as the high and low refractive index materials, and Al2O3 as the protective layer. The film layer thickness is optimized through film design software, and appropriate temperature, vacuum and ion source-assisted deposition parameters are arranged in the coating process.

Benefits of technology

The high transmittance of the silicon-based lens induced film in the 1.8-4μm band is achieved, which meets the requirements of different application ends, and increases the bonding force between the film layer and the substrate, reducing the difficulty of preparation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119511422A_ABST
    Figure CN119511422A_ABST
Patent Text Reader

Abstract

The invention provides a design method and a preparation method of a 1.8-4 [mu] m silicon-based lens anti-reflection film. The design method of the 1.8-4 [mu] m silicon-based lens anti-reflection film comprises the steps that Sa, a film system is designed with 550 nm as the reference wavelength of optical film design, a film stack formula Sub / 0.3 M 0.8 N (HL) 3K / AIR is used, the two faces of Sub are plated with the same film system, Sub is a silicon substrate, AIR represents air, in the film stack formula, H represents a high-refractive-index material ZnS with the 1 / 4 wavelength thickness, L represents a low-refractive-index material YbF3 with the 1 / 4 wavelength thickness, and in the film stack formula, Z represents a high-refractive-index material ZnS with the 1 / 4 wavelength thickness; m represents a base layer material SiO with the thickness of 1 / 4 wavelength, N represents a connecting layer material Ge with the thickness of 1 / 4 wavelength, K represents protective layer materials Al2O3 (aluminum oxide) and Sb with the thickness of 1 / 4 wavelength, and a film layer structure of Sub / SiO / Ge / ZnS / YbF3 / Al2O3 / Air is generated through an input film stack formula; sc, the thickness of the film layer is optimized through thin film design software, the optimal thickness of the film layer is obtained, and the transmittance of the 1.8-4-micron wave band of the optimized film layer structure meets the requirement; and Sd, the optimized film layer thickness is input into a control computer of the coating machine.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of infrared optical film technology, and more specifically to a design method and a preparation method of a 1.8-4 μm silicon-based lens anti-reflection film. Background Art

[0002] Due to its excellent infrared optical and physical properties, silicon has good transparency in the 1.5-14μm band and is widely used in infrared temperature measurement, thermal imaging, uncooled infrared focal plane detection, wafer packaging windows, military guidance and other fields. However, since the silicon substrate is easily oxidized in the atmosphere, the thermal expansion coefficient is quite different from that of common infrared coating materials. In addition, some silicon substrates have convex surfaces (for example, in processes such as laser cutting and welding, silicon convex mirrors can be used to focus and adjust laser beams, improve the accuracy and efficiency of laser processing, and can also be used in optical measuring instruments), resulting in poor bonding between the film layer and the substrate, increasing the difficulty of film preparation. In addition, in the 1.8-4μm band, some commonly used coating materials will have more or less absorption, resulting in low transmittance of the lens after film formation, which cannot meet the requirements of different applications. Therefore, it is more difficult to select coating materials, design film systems, and improve the specific process of coating technology. Summary of the invention

[0003] In view of the problems existing in the background technology, an object of the present disclosure is to provide a design method and a preparation method for a 1.8-4μm silicon-based lens anti-reflection film, which can ensure that the transmittance of the designed and prepared silicon substrate together with the films on both sides meets the requirements in the 1.8-4μm band.

[0004] Another object of the present disclosure is to provide a design method and a preparation method for a 1.8-4 μm silicon-based lens anti-reflection film, which can enable the designed and prepared silicon substrate and the film system on both sides to meet the requirements of different applications.

[0005] Thus, a design method for a 1.8-4μm silicon-based lens anti-reflection film includes the following steps: Sa, the film system design uses 550nm as the reference wavelength for optical film design, and uses the film stack formula: Sub / 0.3M0.8N(HL)^3K / AIR, the same film system is plated on both sides of Sub, wherein Sub is a silicon substrate, AIR represents air, and in the film stack formula, H represents a high refractive index material ZnS (zinc sulfide) with a thickness of 1 / 4 wavelength, and L represents a low refractive index material YbF with a thickness of 1 / 4 wavelength. 3 (Ytterbium fluoride), M represents the 1 / 4 wavelength thickness of the underlying material SiO (silicon monoxide), N represents the 1 / 4 wavelength thickness of the connecting layer material Ge (germanium), K represents the 1 / 4 wavelength thickness of the protective layer material Al 2 O 3(aluminum oxide), Sb, and the film stack formula is input to generate Sub / SiO / Ge / ZnS / YbF 3 / Al 2 O 3 / Air’s film structure; Sc, the film thickness is optimized by thin film design software to obtain the best film thickness. The transmittance of the optimized film structure in the 1.8-4μm band meets the requirements; Sd, the optimized film thickness is input into the control computer of the coating machine.

[0006] A method for preparing a 1.8-4 μm silicon-based lens anti-reflection film comprises the following steps: S1, before plating, cleaning the silicon substrate product and the accompanying plating film as the lens and treating SiO, Ge, ZnS, YbF 3 、Al 2 O 3 Preparation of five kinds of film materials; S2, configuration of coating process conditions and process files, the configuration of coating process conditions and process files includes coating temperature, background vacuum before coating, film thickness, coating mode of film material, deposition rate of film material, use and parameters of ion source assisted deposition, wherein the optimal film thickness is based on the optimal film thickness stored in the control computer of the coating machine in the aforementioned design method of 1.8-4μm silicon-based lens anti-reflection film; S3, put the cleaned lens into the fixture, hang the fixture with the lens in place into the cavity of the coating machine, close the door, draw vacuum and heat; S4, pre-melting of film material; S5, cleaning of lens with ion source; S6, film coating and monitoring, coating the first side of the lens according to the coating process conditions and process files configuration of step S2; S7, maintaining constant temperature after coating; S8, cooling and taking out the parts; S9, repeating steps S1 to S8, coating the second side of the lens.

[0007] The beneficial effects of the present disclosure are as follows.

[0008] In the design method of the 1.8-4μm silicon-based lens anti-reflection film according to the present disclosure, SiO has a similar expansion coefficient to the silicon substrate and is used as a base layer to enhance the bonding between the film layer and the substrate. Ge has good bonding between SiO and Ge and ZnS film layers, but Ge has a large absorption near 1.8μm, so Ge ​​is plated for the connecting layer, and ZnS and YbF 3 As a high and low refractive index material, Al is used to improve the transmittance of the film. 2 O 3 As the outermost protective layer, it is both waterproof and friction-resistant. Therefore, not only the transmittance of the designed film structure in the 1.8-4μm band can meet the requirements, but also the combination of the primer layer and the silicon substrate in the film system on both sides and the requirements of the two-sided film system to meet different application ends are taken into consideration.

[0009] In the method for preparing the 1.8-4μm silicon-based lens anti-reflection film according to the present disclosure, based on steps S1 to S9 and based on the optimal film thickness stored in the control computer of the coating machine in the aforementioned design method for the 1.8-4μm silicon-based lens anti-reflection film, as verified by the test, the transmittance of the prepared silicon-based accompanying coating film together with the film systems on both sides in the 1.8-4μm band can meet the requirements, and at the same time can meet the requirements of bubble test, salt spray test, adhesion test, moderate friction test, constant temperature and humidity test, low temperature test and high temperature test, thereby meeting the requirements of different application ends. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 It is a schematic structural diagram of a silicon substrate and a film system on both sides according to the film stack design and preparation method of the 1.8-4μm silicon-based lens anti-reflection film design method disclosed in the present invention.

[0011] Figure 2 This is a transmittance curve diagram designed by the design method of the 1.8-4μm silicon-based lens anti-reflection film of Example 1.

[0012] Figure 3 This is a transmittance curve diagram of the accompanying coating sheet and the film system on both sides after the coating is completed in the preparation method of the 1.8-4μm silicon-based lens anti-reflection film of Example 1.

[0013] Figure 4 These are photos of the product before and after moderate friction after coating is completed in the method for preparing the 1.8-4 μm silicon-based lens anti-reflection film of Example 1. DETAILED DESCRIPTION

[0014] It is understood that the disclosed embodiments are merely examples of the present disclosure, which may be implemented in various forms, and therefore, the specific details disclosed herein should not be interpreted as limiting, but merely as a basis for the claims and as a representative basis for teaching one of ordinary skill in the art to variously implement the present disclosure.

[0015] [Design method of anti-reflection film for 1.8-4μm silicon-based lenses]

[0016] Reference Figure 1 and Figure 2 The design method of the 1.8-4 μm silicon-based lens anti-reflection film according to the present disclosure comprises the following steps:

[0017] Sa, the film system design uses 550nm as the reference wavelength for optical thin film design, and uses the film stack formula: Sub / 0.3M0.8N(HL)^3K / AIR. The same film system is plated on both sides of Sub, where Sub is the silicon substrate and AIR represents air. In the film stack formula,

[0018] H represents the high refractive index material ZnS (zinc sulfide) with a thickness of 1 / 4 wavelength.

[0019] L represents the low refractive index material YbF with a thickness of 1 / 4 wavelength 3 (Ytterbium fluoride),

[0020] M represents the 1 / 4 wavelength thickness of the underlying material SiO (silicon monoxide),

[0021] N represents the connection layer material Ge (germanium) with a thickness of 1 / 4 wavelength.

[0022] K represents the protective layer material Al with a thickness of 1 / 4 wavelength 2 O 3 (aluminum oxide),

[0023] Sb, through the input film stack formula, generate Sub / SiO / Ge / ZnS / YbF 3 / Al 2 O 3 / Air membrane structure;

[0024] Sc, the film thickness is optimized by thin film design software to obtain the best film thickness. The transmittance of the optimized film structure in the 1.8-4μm band meets the requirements;

[0025] Sd, input the optimized best film thickness into the control computer of the coating machine.

[0026] In the design method of the 1.8-4μm silicon-based lens anti-reflection film according to the present disclosure, SiO has a similar expansion coefficient to the silicon substrate and is used as a base layer to enhance the bonding between the film layer and the substrate. Ge has good bonding between SiO and Ge and ZnS film layers, but Ge has a large absorption near 1.8μm, so Ge ​​is plated for the connecting layer, and ZnS and YbF 3 As a high and low refractive index material, Al is used to improve the transmittance of the film. 2 O 3 As the outermost protective layer, it is both waterproof and friction-resistant. Therefore, not only the transmittance of the designed film structure in the 1.8-4μm band can meet the requirements, but also the combination of the primer layer and the silicon substrate in the film system on both sides and the requirements of the two-sided film system to meet different application ends are taken into consideration.

[0027] In one example, in step Sc, for each of the two sides of the lens, the optimal film thickness is:

[0028] The thickness of the SiO film is 25nm.

[0029] The thickness of the Ge film layer is 25nm.

[0030] The thickness of the ZnS film is 280.31nm.

[0031] The thickness of the YbF3 film is 393.64nm.

[0032] Al 2 O 3 The thickness of the film is 153nm.

[0033] In one example, in step Sc, the average transmittance of the optimized film structure in the 1.8-4 μm band is greater than 99.5%.

[0034] In one example, in step Sa to step Sc, the design software is TFCalc or Essential Macleod.

[0035] [Preparation method of 1.8-4μm silicon-based lens anti-reflection film]

[0036] The method for preparing the 1.8-4 μm silicon-based lens anti-reflection film according to the present disclosure comprises the following steps:

[0037] S1, before plating, the silicon substrate product and the accompanying plating sheet used as the lens are cleaned and SiO, Ge, ZnS, YbF 3 、Al 2 O 3 Preparation of five types of membrane materials;

[0038] S2, configuration of coating process conditions and process files, including coating temperature, background vacuum before coating, film thickness, coating mode of film material, deposition rate of film material, use and parameters of ion source assisted deposition, wherein the optimal film thickness is based on the optimal film thickness stored in the control computer of the coating machine in the aforementioned design method of 1.8-4μm silicon-based lens anti-reflection film;

[0039] S3, the cleaned lens is placed in a fixture, the fixture with the lens is hung in the cavity of the coating machine, and the door is closed to evacuate and heat;

[0040] S4, pre-melting of film material;

[0041] S5, ion source cleaning lens;

[0042] S6, coating and monitoring, coating the first surface of the lens according to the coating process conditions and process file configuration of step S2;

[0043] S7, constant temperature maintenance after coating;

[0044] S8, cooling and picking up;

[0045] S9, repeating steps S1 to S8 to perform film coating on the second surface of the lens.

[0046] In the method for preparing the 1.8-4μm silicon-based lens anti-reflection film according to the present disclosure, based on steps S1 to S9 and based on the optimal film thickness stored in the control computer of the coating machine in the aforementioned design method for the 1.8-4μm silicon-based lens anti-reflection film, as verified by subsequent tests, the transmittance of the prepared silicon-based accompanying coating film together with the film systems on both sides in the 1.8-4μm band can meet the requirements, and at the same time can meet the requirements of blister test, salt spray test, adhesion test, moderate friction test, constant temperature and humidity test, low temperature test and high temperature test, thereby meeting the requirements of different application ends.

[0047] In one example, in step S1, the product is a (50±0.1) mm×(10±0.1) mm convex mirror, and the accompanying plated sheet is a (25±0.1) mm×(2±0.1) mm round sheet.

[0048] The cleaning in step S1 makes the surface of the lens clean, which is conducive to the adhesion and bonding of the film layer. In one example, in step S1, the lens is polished with aluminum oxide polishing liquid and then cleaned with ultrasonic pure water. For example, the aluminum oxide polishing liquid uses a 0.1 μm polycrystalline diamond liquid produced by Nanjing Henry Precision Optics Co., Ltd.

[0049] In one example, in step S2, the coating temperature is 150±2°C; the background vacuum before coating is (1.3±0.1)×10 -3 Pa; the thickness of the film layer in the configuration of the coating process conditions and process files is based on the optimal film thickness stored in the control computer of the coating machine described in the design method of the aforementioned 1.8-4μm silicon-based lens anti-reflection film; the evaporation mode of the film material is: SiO is evaporated by resistance heating, Ge is evaporated by electron beam heating, ZnS and YbF 3 Using resistive heating evaporation, Al 2 O 3 Electron beam heating evaporation is used; the deposition rate of the film material is: the deposition rate of the SiO film layer is The deposition rate of Ge film is The deposition rate of ZnS film is Yb 3 The film deposition rate is AL 2 O 3 The film deposition rate is The use of ion source assisted deposition is as follows: the ion source is not turned on when depositing the Ge film layer, and the ion source is turned on for the other film layers.

[0050] In one example, in step S2, the coating machine is a SEAW 1350.

[0051] In one example, in step S2, the ion source is a Hall source, and the ion source parameters are: neutralization current 0.6±0.01A, neutralization gas flow rate 7±0.1sccm, anode voltage 120±2V, anode current 1±0.01A, no oxygen is added throughout the process, and the proportion of argon in the neutralization gas is 100%.

[0052] In one example, in step S3, the vacuum is first evacuated to 5×10 -2 Pa, and then the chamber of the coating machine starts heating, thereby preventing the silicon substrate from oxidizing under hot and humid conditions.

[0053] In step S4, the film material is pre-melted to release air and remove impurities to ensure the purity of the film material. In one example, in step S4, when the vacuum reaches (4.0-5.0)×10 -3 Pa, the film material is pre-melted. After the film material is pre-melted, the temperature of the chamber of the coating machine reaches 150°C and is kept constant for 10 minutes. Specifically, for example, in step S4, the pre-melting process uses electron beam heating and resistance heating. For SiO film material, the resistance heating current is 620-660mA; for Ge film material, the electron beam heating current is 260-290mA; for ZnS film material, the resistance heating current is 720-760mA; for YbF 3 Film material, resistance heating current is 860-900mA; for Al 2 O 3 Film material, electron beam heating current is 180-210mA.

[0054] The ion source cleaning in step S5 removes the surface oxide layer and attached particles of the silicon substrate, making the surface of the silicon substrate cleaner and increasing the adhesion of the film layer. In one example, in step S5, the vacuum degree of the chamber reaches (1.3±0.1)×10 -3 Pa, start the ion source to perform ion cleaning on the lens, the ion source is a Hall source, the parameters of the ion source are: neutralization current 0.6±0.01A, neutralization gas flow 7±0.1sccm, anode voltage 120±2V, anode current 0.8±0.01A, neutralization gas is argon, and cleaning time is 300±2s.

[0055] In one example, in step S6, when coating each film layer, no gas is introduced into the cavity of the coating machine from outside the coating machine, and the cavity of the coating machine is evacuated and the coating temperature is maintained at 150°C; each film layer is coated at a cavity temperature of 150°C of the coating machine; the crystal oscillator method is used to monitor the film thickness using the corresponding crystal oscillator of the multiple crystal oscillators of the crystal controller, and after the ion source is cleaned, the crystal controller controls the corresponding operation of a new crystal oscillator among the multiple crystal oscillators, and the crystal oscillator frequency is not less than 5850Hz.

[0056] In one example, in step S7, the chamber is kept at 150±2°C for 30 minutes after plating is completed.

[0057] In one example, in step S8, after step S7 is completed, the temperature is first lowered to 130±2°C at 1°C / min and held for 5 minutes, then lowered to 110±2°C at 1°C / min and held for 5 minutes, and finally lowered to below 80±2°C at 1°C / min, and the door is opened to take out the items.

[0058] [test]

[0059] Example 1

[0060] Part 1: Design method of anti-reflection film for 1.8-4μm silicon-based lenses

[0061] The design method of 1.8-4μm silicon-based lens anti-reflection film adopts the following steps:

[0062] Sa, the film system design uses 550nm as the reference wavelength for optical thin film design. In TFCalc, the film stack formula is used: Sub / 0.3M 0.8N(HL)^3K / AIR. The same film system is plated on both sides of Sub, where Sub is the silicon substrate and AIR represents air. In the film stack formula,

[0063] H represents the high refractive index material ZnS (zinc sulfide) with a thickness of 1 / 4 wavelength.

[0064] L represents the low refractive index material YbF with a thickness of 1 / 4 wavelength 3 (Ytterbium fluoride),

[0065] M represents the 1 / 4 wavelength thickness of the underlying material SiO (silicon monoxide),

[0066] N represents the connection layer material Ge (germanium) with a thickness of 1 / 4 wavelength.

[0067] K represents the protective layer material Al with a thickness of 1 / 4 wavelength 2 O 3 (aluminum oxide),

[0068] Sb, through the input film stack formula, generate Sub / SiO / Ge / ZnS / YbF 3 / Al 2 O 3 / Air membrane structure;

[0069] Sc, the film thickness is optimized by thin film design software TFCalc to obtain the best film thickness. The transmittance of the optimized film structure in the 1.8-4μm band meets the requirements.

[0070] In step Sc, for each of the two sides of the lens, the optimal film thickness is:

[0071] The thickness of the SiO film is 25nm.

[0072] The thickness of the Ge film layer is 25nm.

[0073] The thickness of the ZnS film layer is 280.31nm;

[0074] Yb 3 The thickness of the film layer is 393.643nm;

[0075] Al 2 O 3 The thickness of the film is 153nm;

[0076] Sd, the optimized best film thickness is input into the control computer of the coating machine, the coating machine is Siewock 1350.

[0077] Part II: Preparation method of 1.8-4μm silicon-based lens anti-reflection film

[0078] The preparation method of 1.8-4μm silicon-based lens anti-reflection film adopts the following steps:

[0079] S1, before plating, the silicon substrate product and the accompanying plating sheet used as the lens are cleaned and SiO, Ge, ZnS, YbF 3 、Al 2 O 3 Preparation of five kinds of film materials: the product is a 50mm×10mm convex mirror, the accompanying plate is a 25mm×2mm round plate, the lens is polished with alumina polishing liquid, and then ultrasonically cleaned with pure water. The alumina polishing liquid uses a 0.1μm polycrystalline diamond liquid from Nanjing Henry Precision Optics Co., Ltd.;

[0080] S2, configuration of coating process conditions and process files, including coating temperature, background vacuum before coating, film thickness, coating mode of film material, deposition rate of film material, use and parameters of ion source assisted deposition, wherein the optimal film thickness is based on the optimal film thickness stored in the control computer of the coating machine in the design method of 1.8-4μm silicon-based lens anti-reflection film in the first part above,

[0081] In step S2,

[0082] The coating temperature is 150°C;

[0083] The background vacuum before plating is 1.3×10 -3 Pa;

[0084] The thickness of the film layer in the configuration of the coating process conditions and process files is based on the optimal film layer thickness stored in the control computer of the coating machine as described in the design method of the 1.8-4μm silicon-based lens anti-reflection film in the first part above;

[0085] The evaporation modes of the film materials are: SiO is evaporated by resistance heating, Ge is evaporated by electron beam heating, ZnS and YbF are evaporated by 3 Using resistive heating evaporation, Al 2 O 3 Evaporation using electron beam heating;

[0086] The deposition rate of the film material is: The deposition rate of the SiO film layer is The deposition rate of Ge film is The deposition rate of ZnS film is Yb 3 The film deposition rate is

[0087] AL 2 O 3 The film deposition rate is

[0088] The use of ion source assisted deposition is: the ion source is not turned on when depositing the Ge film layer, and the ion source is turned on for the other film layers;

[0089] The ion source is a Hall source, and the ion source parameters are: neutralization current 0.6A, neutralization gas flow rate 7sccm, anode voltage 120V, anode current 1A, no oxygen is added during the whole process, and the proportion of argon in the neutralization gas is 100%.

[0090] S3, put the cleaned lens into the fixture, hang the fixture with the lens into the chamber of the coating machine, close the door, and first vacuumize to 5×10 -2 Pa, after which the coating machine cavity starts heating;

[0091] S4, film material pre-melting, when the vacuum reaches 4.5×10 -3 The film material is pre-melted at Pa. After the pre-melting of the film material is completed, the temperature of the cavity of the coating machine reaches 150°C and is kept constant for 10 minutes.

[0092] In step S4, the pre-melting process uses electron beam heating and resistance heating:

[0093] For SiO film, the current of resistance heating is 640mA

[0094] For Ge film material, the current of electron beam heating is 265mA;

[0095] For ZnS film material, the current of resistance heating is 740mA;

[0096] Targeting YbF 3 Film material, the current of resistance heating is 880mA;

[0097] For Al 2 O 3 Film material, the current of electron beam heating is 195mA;

[0098] S5, ion source cleaning lens, the chamber vacuum reaches 1.3×10 -3 Pa, start the ion source to clean the lens with ions. The ion source is a Hall source. The parameters of the ion source are: neutralization current 0.6A, neutralization gas flow 7sccm, anode voltage 120V, anode current 0.8A, neutralization gas is argon, and cleaning time is 300s;

[0099] S6, coating and monitoring, coating the first surface of the lens according to the coating process conditions and process file configuration of step S2,

[0100] In step S6,

[0101] When coating each film layer, no gas is introduced from outside the coating machine into the coating machine cavity, and the coating machine cavity is kept evacuated and the coating temperature is kept at 150°C;

[0102] Each film layer is coated at a chamber temperature of 150°C in the coating machine;

[0103] The crystal oscillator method uses the corresponding crystal oscillator of the multiple crystal oscillators of the crystal controller to monitor the film thickness. After the ion source is cleaned, the crystal controller controls the corresponding operation of the new crystal oscillator among the multiple crystal oscillators.

[0104] The crystal frequency is 5990Hz;

[0105] S7, after plating is completed, the cavity is kept at 150°C for 30 minutes;

[0106] S8, first cool down to 130℃ at 1℃ / min and hold for 5min, then cool down to 110℃ at 1℃ / min and hold for 5min, finally cool down to 80℃ at 1℃ / min, open the door and take out the items;

[0107] S9, repeating steps S1 to S8 to perform film coating on the second surface of the lens.

[0108] Comparative Example 1

[0109] Except that the ion source with the same parameters is also turned on during the deposition of the Ge film in step S2, the rest is the same as in Example 1.

[0110] Comparative Example 2

[0111] Except in step S1, step S2, and step S4, use Y2 O 3 Al 2 O 3 Except that only the film material is changed, the rest is the same as in Example 1.

[0112] Comparative Example 3

[0113] Except that Si is used to replace SiO in step S1, step S2 and step S4 (that is, only the film material is changed), the rest is the same as in Example 1.

[0114] Comparative Example 4

[0115] Except that the coating temperature in step S2 is 180°C, the temperature of the cavity of the coating machine in step S4 reaches 180°C, the coating temperature is maintained at 180°C in step S6, and each film layer is plated at a temperature of 180°C in the cavity of the coating machine, the rest is the same as Example 1.

[0116] Comparative Example 5

[0117] Except for the background vacuum before plating in step S2, which is 4.0×10 -3 Pa, the vacuum degree of the chamber in step S5 reaches 4.0×10 - 3 Except for Pa, the rest is the same as in Example 1.

[0118] Comparative Example 6

[0119] Except that in step S2, the Ge film deposition rate is And YbF 3 The film deposition rate is Other than that, the same as in Example 1.

[0120] Comparative Example 7

[0121] Except that in step S2, the ion source parameters are filled with oxygen throughout the process, the total flow rate of the neutralizing gas is 10 sccm, and the ratio of argon gas to oxygen is 7:3, the rest are the same as in Example 1.

[0122] Comparative Example 8

[0123] In addition to introducing argon gas from the outside of the coating machine into the cavity of the coating machine in step S6 and keeping the cavity of the coating machine evacuated and ensuring that the coating vacuum is maintained at 5×10 -3 Except for Pa, the rest is the same as in Example 1.

[0124] Figure 2 1.8-4μm silicon-based lens anti-reflection film design method of Example 1 is designed with a transmittance curve. Figure 2 It can be seen that the average transmittance of the silicon substrate together with the films on both sides in the 1.8-4μm band is 99.7%.

[0125] Figure 3 The transmittance curve of the accompanying plate and the film system on both sides after the coating is completed in the preparation method of the 1.8-4μm silicon-based lens anti-reflection film of Example 1. Figure 3 It can be seen that the average transmittance of the accompanying plate together with the films on both sides in the 1.8-4μm band is 98.6% (ie, more than 98%).

[0126] The average transmittance of the accompanying coating sheets of Comparative Examples 1-8 together with the films on both sides in the 1.8-4 μm band is listed in Table 1.

[0127] The products of Example 1 and Comparative Examples 1-8, together with the membrane systems on both sides, were subjected to the following overall performance test.

[0128] Water bubble test: Take tap water to conduct a water bubble test for 2 hours to observe whether the film layer on each surface falls off or cracks.

[0129] Salt spray test: neutral salt spray test for 24 hours, observe whether the film layer on each surface falls off or cracks.

[0130] Adhesion test: Use your hands to stick 3M tape on each side and pull the tape in the direction opposite to the sticking end to see if the film layer is pulled up.

[0131] Moderate friction test: The film layer is rubbed 50 times with a rubber friction head wrapped with degreased cloth at a pressure of 4.9N, and observe whether there are scratches or damage.

[0132] Constant temperature and humidity test: In a constant temperature and humidity chamber, at 50°C and 95% relative humidity for 24 hours, observe whether the film layers on each surface fall off or crack.

[0133] Low temperature test: In a low temperature box, at -40℃ for 24 hours, observe whether the film layers on each surface fall off or crack.

[0134] High temperature test: In a high temperature box, 85℃ for 24 hours, observe whether the film layers on each surface fall off or crack.

[0135] Table 1 shows the average transmittance of Example 1 and Comparative Examples 1-8 and the results of various tests

[0136] Table 1 Average transmittance of Example 1 and Comparative Examples 1-8 and results of various tests

[0137]

[0138] Figure 4 The following are photos of the product before and after moderate friction after the coating is completed in the method for preparing the 1.8-4 μm silicon-based lens anti-reflection film of Example 1.

[0139] The above detailed description is used to describe multiple exemplary embodiments, but this document is not intended to be limited to the explicitly disclosed combinations. Therefore, unless otherwise stated, the various features disclosed herein can be combined together to form multiple additional combinations that are not shown for the sake of simplicity.

Claims

1. A design method for a 1.8-4 μm silicon-based lens anti-reflection film, characterized in that: Includes steps: Sa, the film system design uses 550nm as the reference wavelength for optical thin film design, and uses the film stack formula: Sub / 0.3M 0.8N(HL)^3K / AIR. The same film system is plated on both sides of Sub, where Sub is the silicon substrate and AIR represents air. In the film stack formula, H represents the high refractive index material ZnS (zinc sulfide) with a thickness of 1 / 4 wavelength. L represents the low refractive index material YbF3 (ytterbium fluoride) with a thickness of 1 / 4 wavelength. M represents the 1 / 4 wavelength thickness of the underlying material SiO (silicon monoxide), N represents the connection layer material Ge (germanium) with a thickness of 1 / 4 wavelength. K represents the protective layer material Al2O3 (aluminum oxide) with a thickness of 1 / 4 wavelength. Sb, through the input film stack formula, generates the film layer structure of Sub / SiO / Ge / ZnS / YbF3 / Al2O3 / Air; Sc, the film thickness is optimized by thin film design software to obtain the best film thickness. The transmittance of the optimized film structure in the 1.8-4μm band meets the requirements; Sd, the optimized film thickness is input into the control computer of the coating machine.

2. The design method of 1.8-4 μm silicon-based lens anti-reflection film according to claim 1, characterized in that: In step Sc, for each of the two sides of the lens, the optimal film thickness is: The thickness of the SiO film is 25nm. The thickness of the Ge film layer is 25nm. The thickness of the ZnS film is 280.31nm. The thickness of the YbF3 film is 393.64nm. The thickness of the Al2O3 film is 15nm; In step Sc, the average transmittance of the optimized film structure in the 1.8-4 μm band is greater than 99.5%.

3. A method for preparing a 1.8-4 μm silicon-based lens anti-reflection film, characterized in that: Includes steps: S1, before plating, the silicon substrate product and the accompanying plating sheet used as the lens are cleaned and five kinds of film materials, SiO, Ge, ZnS, YbF3 and Al2O3, are prepared; S2, configuration of coating process conditions and process files, the configuration of coating process conditions and process files includes coating temperature, background vacuum before coating, film thickness, coating mode of film material, deposition rate of film material, use and parameters of ion source assisted deposition, wherein the optimal film thickness is based on the optimal film thickness stored in the control computer of the coating machine according to any one of claims 1-2; S3, the cleaned lens is placed in a fixture, the fixture with the lens is hung in the cavity of the coating machine, and the door is closed to evacuate and heat; S4, pre-melting of film material; S5, ion source cleaning lens; S6, coating and monitoring, coating the first surface of the lens according to the coating process conditions and process file configuration of step S2; S7, constant temperature maintenance after coating; S8, cooling and picking up; S9, repeating steps S1 to S8 to perform film coating on the second surface of the lens.

4. The method for preparing a 1.8-4 μm silicon-based lens antireflection film according to claim 3, characterized in that: In step S1, The product is a (50±0.1)mm×(10±0.1)mm convex mirror, and the accompanying plate is a (25±0.1)mm×(2±0.1)mm round plate. The lenses are polished with aluminum oxide polishing liquid and then cleaned with ultrasonic pure water.

5. The method for preparing a 1.8-4 μm silicon-based lens antireflection film according to claim 3, characterized in that: In step S2, The coating temperature is 150±2℃; The background vacuum before plating is (1.3±0.1)×10 -3 Pa; Coating process conditions and film thickness in the configuration of process files Based on the optimal film thickness stored in the control computer of the coating machine according to claim 2; The evaporation modes of the film materials are: SiO is evaporated by resistance heating, Ge is evaporated by electron beam heating, ZnS and YbF3 are evaporated by resistance heating, and Al2O3 is evaporated by electron beam heating; The deposition rate of the film material is: The deposition rate of the SiO film layer is The deposition rate of Ge film is The deposition rate of ZnS film is The deposition rate of YbF3 film is The deposition rate of AL2O3 film is The use of ion source assisted deposition is: the ion source is not turned on when depositing the Ge film layer, and the ion source is turned on for the other film layers; The ion source is a Hall source, and the ion source parameters are: neutralization current 0.6±0.01A, neutralization gas flow rate 7±0.1sccm, anode voltage 120±2V, anode current 1±0.01A, no oxygen is added during the whole process, and the proportion of argon in the neutralization gas is 100%.

6. The method for preparing a 1.8-4 μm silicon-based lens antireflection film according to claim 3, characterized in that: In step S3, the vacuum is first evacuated to 5×10 -2 Pa, after which the coating machine's cavity starts heating.

7. The method for preparing a 1.8-4 μm silicon-based lens antireflection film according to claim 3, characterized in that: In step S4, when the vacuum reaches (4.0-5.0)×10 -3 The film material is pre-melted at Pa. After the pre-melting of the film material is completed, the temperature of the cavity of the coating machine reaches 150°C and is kept constant for 10 minutes. The pre-melting process uses electron beam heating and resistance heating. For SiO film materials, the current of resistance heating is 620-660mA; For Ge film material, the current of electron beam heating is 260-290mA; For ZnS film material, the current of resistance heating is 720-760mA; For YbF3 film material, the current of resistance heating is 860-900mA; For Al2O3 film materials, the current of electron beam heating is 180-210mA.

8. The method for preparing a 1.8-4 μm silicon-based lens antireflection film according to claim 3, characterized in that: In step S5, The vacuum degree of the cavity reaches (1.3±0.1)×10 -3 Pa, start the ion source to perform ion cleaning on the lens, the ion source is a Hall source, the parameters of the ion source are: neutralization current 0.6±0.01A, neutralization gas flow 7±0.1sccm, anode voltage 120±2V, anode current 0.8±0.01A, neutralization gas is argon, and cleaning time is 300±2s.

9. The method for preparing a 1.8-4 μm silicon-based lens antireflection film according to claim 3, characterized in that: In step S6, When coating each film layer, do not introduce any gas from outside the coating machine into the coating machine cavity and keep the coating machine cavity evacuated, and keep the coating temperature at 150°C; Each film layer is coated at a chamber temperature of 150°C in the coating machine; The crystal oscillator method is used to monitor the film thickness using the corresponding crystal oscillator pieces of the multiple crystal oscillator pieces of the crystal controller. After the ion source is cleaned, the crystal controller controls the corresponding operation of the new crystal oscillator pieces among the multiple crystal oscillator pieces, and the crystal oscillator frequency is not less than 5850Hz.

10. The method for preparing a 1.8-4 μm silicon-based lens antireflection film according to claim 3, characterized in that: In step S7, after the plating is completed, the cavity is kept at 150±2°C for 30 minutes; In step S8, after step S7 is completed, the temperature is first lowered to 130±2°C at 1°C / min and held for 5 minutes, then lowered to 110±2°C at 1°C / min and held for 5 minutes, and finally lowered to below 80±2°C at 1°C / min, and the door is opened to take out the items.

Citation Information

Patent Citations

  • Super wide band cut-off long-wave-pass filter optical film and production method thereof

    CN103207424A

  • Laser, medium-wave infrared and long-wave infrared composite antireflection thin film with chalcogenide glass substrate

    CN111090134A

  • 8-12 [mu] m waveband HD film infrared germanium diaphragm

    CN116577850A

  • Mould pressing chalcogenide glass lens and preparation method of near-infrared antireflection film plated on mould pressing chalcogenide glass lens

    CN117388960A

  • Medium-wave infrared anti-reflection film suitable for wide-angle incidence and preparation method of medium-wave infrared anti-reflection film

    CN117761806A

Cited By

  • High-transmittance film of laser, preparation method of high-transmittance film and high-power pulse laser

    CN120914594A